(-3 ) x ( + 3 )=( - 3) * ( - 3)= ______
2 ( - 3) * ( - 3)=
3) ( + 20 ) ( + 5) = ____

4) ( + 21 ) ( - 3 ) )= ___

5) (-2) * (+3) * (- 4) = ___

6) __ (5 + 4) = 2 * 5 + 2 * 4

7) 8 * 7 + 8 * 3 = 8 (7 + ___ )

8) 6 * 5 – 6 * 2 = 6 (__ - __)

9) 5 * 3 + 10 * 3 = 3( __ + 10)

10) 8 * 4 – 8 * 2 = ___ (4 – 2)

11) 7 ( 5 – 2 ) = 7 * ___

12) 5 (2 + 4 ) = 5 * ___

13) ( 64 8 ) 2 = ___

14) 2 * ( 9 + 1 ) = 2 * ___

15) ( 100 + 10 ) 5 = _____

16) (100 – 40 ) 10 = ____

17) – 5 * 5 = ____

18) 5 * ( -6 ) = ____

19) ( + 2 ) X ( + 3) = ___

20) ( + 6 ) X ( - 2 ) = ____